Development and Feasibility Test of UNO Card Learning Media to Improve Understanding of Kāna wa Akhwātuhā Material in Islamic High School Students: A Study at MAN 20 Jakarta - Ihwan Rahman Bahtiar; Devina Firda Amalia; Fatwa Arifah; Mohamad Sarip; Siti Masyitoh (Universitas Ahmad Dahlan, 2026)
Due to the abstract nature of Arabic grammar and the lack of engaging classroom resources, students often struggle to understand kāna wa akhwātuhā material. To enhance students' understanding of the subject, this study aims to develop and evaluate the viability and effectiveness of UNO-based learning materials. The R&D methodology for this study used the ADDIE model, which comprises the stages of analysis, design, development, implementation, and evaluation. Students from MAN 20 Jakarta carried out the study. Questionnaires, expert validation sheets, and pre- and post-test instruments were used for data collection. Expert validation and positive student responses, both classified as very achievable, indicate that the developed media are very achievable. In addition, the performance test shows a high N-Gain and increased average scores, indicating a significant improvement in student achievement. This study focuses on the teaching of kāna wa akhwātuhā and progresses towards the production of game-based Arabic grammar teaching material. UNO cards are an alternative learning tool that can help create a more dynamic, engaging, and student-centered learning environment.